Drug Use in Medical Perspective and Islamic Law - Rahmadhani; Irsyam Risdawati (International Journal of Synergy in Law, Criminal, and Justice, 2024)
The use of Narcotics, Psychotropics and Addictive Substances (NAPZA), including marijuana, presents a dilemma in the medical and legal context, especially in Indonesia. While several countries have recognized the medical benefits of marijuana, Indonesia still classifies it as a Class I narcotic, the abuse of which is subject to heavy sanctions. This research examines the duality of marijuana use, which on the one hand has significant therapeutic potential, and on the other hand, presents risks of abuse and serious legal implications in accordance with Law no. 35 of 2009 concerning Narcotics. This research also considers the views of Islamic law regarding the use of substances that can affect psychological and physiological conditions. This research uses a normative juridical approach, analyzing existing regulations, Islamic legal texts, and academic literature to explore the medical and legal implications of using marijuana as medicine. Research results show that marijuana has therapeutic benefits that cannot be ignored, especially in treating chronic and serious diseases such as epilepsy, glaucoma and cancer. However, strict regulations and existing stigma hinder this potential utilization. Revision of Law no. 35 of 2009 to consider the medical potential of marijuana, with more flexible regulations that allow research and controlled use of marijuana for medical purposes. Further studies are needed to support these policy changes, ensuring that cannabis use can occur within a safe and responsible framework. Keywords:Medical Marijuana, Narcotics Law, Islamic Law, Narcotics Policy, Marijuana Research.